Resistance advocacy as news : digital black press covers the tea party - LaPoe, Benjamin Rex; LaPoe, Victoria, 1977- (Lexington Books, 2018)
This book examines the Black and mainstream press's digital interpretations of the Tea Party during President Barack Obama's first term. It addresses questions surrounding the idea of our society as one that is "postracial" and the ongoing struggle of Black people to have their voices heard in the mainstream press.